ANALISIS PERANAN AKTA KONSEN ROYA DALAM ROYA HAK TANGGUNGAN YANG HAK TANGGUNGANNYA DIPERPANJANG - DESI PRANATA SIMAMORA (PREMISE LAW JURNAL, 2017)
A hypothecation is the right over a mortgaged piece of land as stipulated in the Law No. 5/1960 on Land Act, along with or without other things which constitute to the land, to pay off a certain debt, which puts one particular creditor in higher priority than the others. When a debtor wants to pay off all his debts with the extended hypothecation and the Hypothecation Certificate is missing, the Notary makes Cancellation Consent Deed or Cancellation Hypothecation Permit Deed. The results show that the role of Cancellation Consent Deed is necessary to substitute the missing Hypothecation Certificate. It plays the role of a living law. Some Notaries mention that the clause is based on the report of missing, but some others do not mention it in the deed. This difference does not lead to a dispute because it is not specifically regulated. Due to the frequency, this habit can be said to be legally acceptable without any regulation and it applies to any party and there is not any rejection from any party to it. Keywords: Hypothecation Right, Credit, Cancellation, Cancellation Consent